2015
DOI: 10.1155/2015/685821
|View full text |Cite
|
Sign up to set email alerts
|

Viral Agents of Diarrhea in Young Children in Two Primary Health Centers in Edo State, Nigeria

Abstract: Enteric viruses have been shown to be responsible for diarrhea among children during their early childhood. This study was carried out to determine the prevalence of rotavirus, adenovirus, and norovirus infection in young children with diarrhea in two primary health centers in Edo State, Nigeria. A total of 223 stool specimens were collected from children aged 0–36 months with clinical signs of diarrhea and 59 apparently healthy age-matched children as control. These specimens were investigated for three viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
6
19
2
Order By: Relevance
“…Comparing the EVs, the age distribution of patients with viral gastroenteritis was not statistically significant, but they were detected mainly in children 0 to 24 months, which is in agreement with reports from Nigeria . Consistent with the findings from Angola, Gabon, and Nigeria, the burden of viral gastroenteritis in this study is predominantly in males, although there was no significant association.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Comparing the EVs, the age distribution of patients with viral gastroenteritis was not statistically significant, but they were detected mainly in children 0 to 24 months, which is in agreement with reports from Nigeria . Consistent with the findings from Angola, Gabon, and Nigeria, the burden of viral gastroenteritis in this study is predominantly in males, although there was no significant association.…”
Section: Discussionsupporting
confidence: 88%
“…Worldwide, RVA is responsible for many deaths, mainly among young children in Asia and Africa . RVA was detected in 16.6% cases, which is lower to studies from Angola, Burkina Faso, Northern Italy, Enugu, and Edo States, Nigeria . Both NoV and HAdV in this study were found in 5.1% of children with gastroenteritis which is similar to that reported in Republic Democratic of Congo and North East, Nigeria but lower compared with studies in Albania, Burkina Faso, Northern Italy, and Ondo State, Nigeria .…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Epidemiological data have shown that both viruses are circulating around the world, with prevalence rates of 16.2-19.3% for HAdV detected by immunochromatography 4,5 and 0.8-5% for SaV 6,7 detected by reverse transcription polymerase chain reaction (RT-PCR). In Brazil, some investigations have reported HAdV and SaV infections among hospitalized children in the Northern Region, with prevalence rates of 2-10% and 2.5-5.9%, respectively, based on enzyme immunoassay (EIA), PCR, and RT-PCR methodologies [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%